2017
DOI: 10.1016/j.jtcvs.2016.10.078
|View full text |Cite
|
Sign up to set email alerts
|

Development and impact of arrhythmias after the Norwood procedure: A report from the Pediatric Heart Network

Abstract: Objectives The study objective was to determine the predictors of new-onset arrhythmia among infants with single-ventricle anomalies during the post-Norwood hospitalization and the association of those arrhythmias with postoperative outcomes (ventilator time and length of stay) and interstage mortality. Methods After excluding patients with preoperative arrhythmias, we used data from the Pediatric Heart Network Single Ventricle Reconstruction Trial to identify risk factors for tachyarrhythmias (atrial fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…They also found that although all postoperative arrhythmias were associated with prolonged recovery, only atrioventricular block was associated with diminished transplant-free survival. 2 Tachyarrhythmia was not infrequent in this study, and was associated with prolonged recovery, although not with diminished survival. 2 Conclusions from this study, though, are restricted by several limitations.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 49%
See 4 more Smart Citations
“…They also found that although all postoperative arrhythmias were associated with prolonged recovery, only atrioventricular block was associated with diminished transplant-free survival. 2 Tachyarrhythmia was not infrequent in this study, and was associated with prolonged recovery, although not with diminished survival. 2 Conclusions from this study, though, are restricted by several limitations.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 49%
“…2 Tachyarrhythmia was not infrequent in this study, and was associated with prolonged recovery, although not with diminished survival. 2 Conclusions from this study, though, are restricted by several limitations. The etiology of tachyarrhythmia is unclear and can be multifactorial, related to metabolic, anatomic, surgical, and demographic factors.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 49%
See 3 more Smart Citations